Lorenzo Palacios, Chacalón: A Popular Idol of the 21st Century - Quispe Lázaro, Arturo (2023)
In this article, I will address the social and cultural processes involved in the shaping and popularity of the popular idol of Peruvian tropical music—chicha —, «Papá Chacalón.» He was a singer who emerged from the most marginalized sectors of Lima society. Among his followers are mayors, prisoners serving their sentence in jail, as well as men and women from the poor neighborhoods of Lima. Several decades after his death, there is a new legion of fans, «chicheros chacaloneros» (Chacalón’s followers). The popular idol, in this context, is configured based on and from the daily relationship between Chacalón and his followers. In this work, I will place special emphasis on the idol-follower relationship, the forms of social interaction, and the cultural assessments involved. I will posit that the ideas of equality and social recognition are central elements in the construction of «Papá Chacalón» as a popular idol and his continuity in the 21st century. This is an ethnographic work carried out during the anniversary festivities of Chacalón, held on April 26 (his birthdate) and June 24 (the day of his death), which also addresses how his followers organize around those dates.